Kesehatan Mental pada Wanita Karir yang Menjadi Orang Tua Tunggal: Analisis Faktor Penyebab dan Strategi Penanganan - Muhamad Fajri; Karmila Karmila (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The phenomenon of single mothers who also work as career women is increasingly prevalent in Indonesia. The dual responsibility as both breadwinner and primary caregiver causes high psychological pressure, leading to mental health problems such as stress, anxiety, and burnout. Objective : This study aims to analyze the factors causing mental health disorders among career women who are single parents and to identify effective coping strategies to maintain their psychological well-being. Research Methods/ Implementation Methods : Implementation Methods : This research uses a qualitative descriptive method through a literature review approach. Data are collected from relevant national and international journal articles published after 2020 that discuss mental health, burnout, and coping mechanisms among single working mothers. Results : The results show that the main factors influencing mental health disorders in single- parent career women include parenting guilt, economic pressure, and role overload. These factors contribute to chronic stress and burnout, especially when social and organizational support is limited. Effective coping strategies identified include self-compassion, mindfulness, social support networks, and flexible work policies that promote work-life balance. Conclusion/Lesson Learned : Mental health issues among single-parent career women are caused by a combination of psychological, social, and structural stressors. Strengthening coping strategies, social support, and organizational flexibility can significantly improve their resilience and mental well-being. Addressing these factors holistically helps single mothers perform their dual roles sustainably without compromising personal or family health.